2022
DOI: 10.1093/brain/awac235
|View full text |Cite
|
Sign up to set email alerts
|

Spinal cord associative plasticity improves forelimb sensorimotor function after cervical injury

Abstract: Associative plasticity occurs when two stimuli converge on a common neural target. Previous efforts to promote associative plasticity have targeted cortex, with variable and moderate effects. In addition, the targeted circuits are inferred, rather than tested directly. In contrast, we sought to target the strong convergence between motor and sensory systems in the spinal cord. We developed spinal cord associative plasticity, precisely timed pairing of motor cortex and dorsal spinal cord stimulat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
22
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(27 citation statements)
references
References 63 publications
5
22
0
Order By: Relevance
“…Electrical stimulation of afferents activates motoneurons through circuits involved in reflexes ( 19 , 20 ). This mechanism has been corroborated by mathematical modeling of current flow ( 21 23 ) as well as in inactivation studies ( 14 ). Consistent with this model, we have shown that stimulating near the dorsal root entry zone is more effective than stimulating at midline in the cervical spinal cord of rats ( 24 ).…”
Section: Introductionmentioning
confidence: 60%
“…Electrical stimulation of afferents activates motoneurons through circuits involved in reflexes ( 19 , 20 ). This mechanism has been corroborated by mathematical modeling of current flow ( 21 23 ) as well as in inactivation studies ( 14 ). Consistent with this model, we have shown that stimulating near the dorsal root entry zone is more effective than stimulating at midline in the cervical spinal cord of rats ( 24 ).…”
Section: Introductionmentioning
confidence: 60%
“…In previous work we found that the facilitatory effects of combined brain and spinal stimulation were strong in both uninjured (Mishra et al 2017) and spinal cord injured (Pal et al 2022) rats. Consistent with this, there was no relationship between MEP augmentation and radiographic (T2 signal) or clinical evidence of myelopathy (mJOA, reflexes).…”
Section: Resultsmentioning
confidence: 92%
“…Epidural spinal cord stimulation recruits a large number of sensory axons as they enter the spinal cord (Capogrosso et al 2013; Liang et al 2023; McIntosh et al 2023). In one preclinical study, our group showed that timing motor cortex and dorsal epidural spinal stimulation to converge in the spinal cord markedly increased the motor evoked potential (MEP) (by 155%), while convergence in motor cortex resulted in a much smaller effect (17%) (Pal et al 2022). We have shown this method of paired stimulation targeted at sensorimotor interactions in the spinal cord to induce plasticity (Mishra et al 2017) and improve dexterity in rats with spinal cord injury (Pal et al 2022).…”
Section: Introductionmentioning
confidence: 99%
“…After all, maladaptive neural activity was allowed to develop unchecked and to chronify naturally, resulting in a 'worst case scenario' for plasticity-promoting interventions. And whereas preclinical and clinical studies have repeatedly demonstrated the ability of motor-dominant circuits below a lesion to beneficially and durably reorganize (25)(26)(27)(28)(29)(30)(31)(32), neural transmission in spinal pain pathways has been comparatively difficult to shape. Indeed, interventions explicitly designed to promote functionally-relevant neural plasticity as well as those that attempt to pharmacologically rebalance spinal excitability have been met with variable and generally nominal successespecially when initiated after establishment of the neuropathic pain state (33,34).…”
Section: Discussionmentioning
confidence: 99%
“…As a result, the ISMS paradigm made no explicit attempts to restore or reinforce natural, appropriate patterns of neural transmission in the modulated networks. Previously, it has been shown that activity-dependent spinal stimulation leads to functional gains that far exceed those afforded by open-loop stimulation, presumably by more optimally engaging circuits below the injury to promote beneficial neural plasticity (25,27,39,40).…”
Section: Discussionmentioning
confidence: 99%